The Clinicopathological Impact of Granulocyte-Macrophage Colony-Stimulating Factor Gene Expression and Different Molecular Prognostic Biomarkers in Egyptian Acute Myeloid Leukemia Patients - Nagdy, Bassant (Asian Pac J Cancer Prev, 2020)
BACKGROUND: Acute myeloid leukemia (AML) is characterized by clonal expansion of myeloid precursors with diminished capacity for differentiation. It develops as the consequence of a series of genetic changes in a hematopoietic precursor cell. Purpose This study aimed to investigate the correlation between GM-CSF gene expression and different molecular prognostic markers such as FLT3-ITD, NPM1 mutation A and CEBPA gene expression in 100 Egyptian AML patients. As well as, correlation with the response to induction therapy, DFS andOS in these patients. METHODOLOGY: Quantitative assessment of GM-CSF gene expression was performed by qRT-PCR. Additional prognostic molecular markers were determined as FLT3-ITD and NPM1 mutation A together with quantitative assessment of CEBPA gene expression by qRT-PCR. RESULTS: Patients with high GM-CSF expression levels had better OS and DFS with p value 0.004 and 0.02, respectively. However, no statistically significant difference between low andhigh GM-CSF gene expression was found regarding the response to therapy (p value= 0.08). Most patients with low CEBPA expression had resistant disease together with poor OS and DFS (P value = <0.001 for each). Our results showed that patients with high CEBPA gene expression whether GM-CSF gene expression was high or low had significant higher complete remission rates (p value = 0.1 for each). However, low GM-CSF gene expression andlow CEBPA gene expression showed poor response to treatment. CONCLUSION: Our findings suggest that molecular diagnostic biomarkers for AML are an essential tool that improves prognostication andhence better patients’ management.